Self-Interest Conflict as the Potential Threat for Audit Quality (A Case Study in KAP KBAA Malang Branch) - Alam Baskara, Rizal Agung; Djamhuri, Ali (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Globalization is now occurred and brings many pressures to both of local and multinational companies. Their stakeholders demand good performance from their companies, specifically through their financial report. The data are obtained through interviews. After that, the results were analysed based conflict of interest theory and evaluated to give some suggestions that can be useful for the firm and management. Based on the results of evaluation, KAP Krisnawan, Busroni, Achsin and Alamsyah (KBAA) Malang Branch has an adequate operational system to avoid any conflict of interest and to maintain its operation through globalization. Some improvements have to be made in the aspect of work areas, organization structure and monitoring, In regard to that, operational system can be more effective and efficient in the future. Key word: self-interest conflict, auditing, globalization